Inequality aversion and the long-run effectiveness of monetary policy: Bilateral versus group comparison - Steffen Ahrens (Kiel Institute for the World Economy (IfW), 2012)
In this paper we incorporate the two most prominent approaches of inequality aversion, i.e. Fehr and Schmidt (1999) and Bolton and Ockenfels (2000) into an otherwise standard New Keynesian macro model and compare them with respect to their influence on the long-run effectiveness of monetary policy. We find that the choice for Fehr and Schmidt or Bolton and Ockenfels like preferences is of importance only for the quantitative - but not the qualitative - effectiveness of monetary policy in the long-run.
Keywords: D03; E20; E31; E50; 330; price stickiness; long-run Phillips curve; inequality aversion